The Impact of Psychological Intervention on Some Psychosocial Variables in Iraqi Futsal Players - Atiyah Sowir , Hussein; Abdi, Hassan; Hoossein Algnabe, Akram; Faraeen, Maryam; Badami, Rokhsareh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The aim of this study was to examine the impact of psychological intervention on some psychosocial variables in Iraqi futsal players.Methods and Materials: The research method was quasi-experimental, and the design included pre-test and post-test with control and experimental groups. The statistical population consisted of Iraqi futsal players from Baghdad, aged 20 to 30 years. Thirty individuals were selected based on inclusion and exclusion criteria, and on a voluntary and accessible basis. The participants were randomly assigned into two groups of 15 (one control group and one experimental group). The research questionnaires included the Sports Mental Toughness Questionnaire (SMTQ), the Competitive State Anxiety Inventory-2R (CSAI-2R), and the Athlete Coping Skills Inventory (ACSI-28). The research protocol involved a ten-session psychological skills training intervention (PSTMI), including one introductory session, eight skill-focused sessions (goal setting, mental imagery, mindfulness/activation regulation, and self-talk), and one concluding session based on the study by Josephson et al. (2017). Data analysis was performed using a one-way analysis of covariance (ANCOVA). All statistical operations were conducted using SPSS version 25, with a significance level set at p < 0.05.Findings: The results showed that, after controlling for the pre-test effects, the difference in pre-test and post-test scores between the two groups for the variables of competitive anxiety, mental toughness, and coping skills was significant (p < 0.001).Discussion and Conclusion: Therefore, it can be concluded that mindfulness intervention and psychological skills training are effective in reducing competitive anxiety and increasing mental toughness and coping skills among Iraqi futsal players.